Analisis Kinerja Keuangan Diukur dari Rasio Likuiditas dan Solvabilitas pada CV. Cipta Lestari Group - Eddi Suprayitno (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2022)
This research is to determine the company's financial performance CV. Cipta Lestari Group in terms of liquidity and solvency and to find out the dominant ratio that increases the performance of CV. Cipta Lestari Group Medan. Financial performance can be interpreted as a prospect or future, growth and good development potential for the company. There are various ways that can be done to assess a company, one of which is by analyzing the company's financial performance using financial ratios. Data collection techniques using interviews and documentation. Data analysis techniques using descriptive analysis and comparative analysis. The results of this study indicate that the company's financial performance is not good. Financial performance is measured by the ratio of liquidity and solvency (DAR, DER) showing illiquid and insolvable results.